Association of plasma cell-free DNA with survival in patients with IDH wild-type glioblastoma. Issue 1 (16th January 2021) - Bagley, Stephen J; Till, Jacob; Abdalla, Aseel; Sangha, Hareena K; Yee, Stephanie S; Freedman, Jake; Black, Taylor A; Hussain, Jasmin; Binder, Zev A; Brem, Steven; Desai, Arati S; O'Rourke, Donald M; et al.
Abstract: Background: We aimed to determine whether plasma cell-free DNA (cfDNA) concentration is associated with survival in patients with isocitrate dehydrogenase ( IDH ) wild-type glioblastoma (GBM). Methods: Pre-operative and post-chemoradiotherapy blood samples were prospectively collected from patients with newly diagnosed IDH wild-type GBM. Patients underwent surgical resection or biopsy and received adjuvant radiotherapy with concomitant temozolomide. Cell-free DNA (cfDNA) was isolated from plasma and quantified using SYBR Green-based q polymerase chain reaction (qPCR). Results: Sixty-two patients were enrolled and categorized into high vs. low cfDNA groups relative to the pre-operative median value (25.2 ng/mL, range 5.7–153.0 ng/mL). High pre-operative cfDNA concentration was associated with inferior PFS (median progression-free survival (PFS), 3.4 vs. 7.7 months; log-rank P = .004; hazard ratio [HR], 2.19; 95% CI, 1.26–3.81) and overall survival (OS) (median OS, 8.0 vs. 13.9 months; log-rank P = .01; HR, 2.43; 95% CI, 1.19–4.95). After adjusting for risk factors, including O 6 -methylguanine-DNA methyltransferase ( MGMT ) promoter methylation status, pre-operative cfDNA remained independently associated with PFS (HR, 2.70; 95% CI, 1.50–4.83; P = .001) and OS (HR, 2.65; 95% CI, 1.25–5.59; P = .01). Post-hoc analysis of change in cfDNA post-chemoradiotherapy compared to pre-surgery ( n = 24) showed increasing cfDNA concentration was associated with worse PFS (median, 2.7 vs. 6.0 months; log-rank P = .003; HR, 4.92; 95% CI, 1.53–15.84) and OS (median, 3.9 vs. 19.4 months; log-rank P < .001; HR, 7.77; 95% CI, 2.17–27.76). Conclusions: cfDNA concentration is a promising prognostic biomarker for patients with IDH wild-type GBM. Plasma cfDNA can be obtained noninvasively and may enable more accurate estimates of survival and effective clinical trial stratification.